(untitled) (Bangladesh Journal of Botany, 2026)
The dragon (Selenicereus costaricensis F.A.C. Weber) fruit is an important fruit crop of India. In the present study, shoot tips of S. costaricensis were used as explants and were inoculated into MS medium supplemented with different growth regulator combinations to produce quality and genuine planting materials. Maximum shoot initiation and proliferation were observed on MS medium supplemented with 3 mg/l BAP + 0.5 mg/l NAA + 1 mg/l Kn. Similarly, maximum number of multiple shoots (8) and highest shoot length (4.05 cm) were noticed on MS medium supplemented with 7 mg/l of BAP + 0.5 mg/l NAA + 1 mg/l Kn. However, maximum root proliferation (82.50%) and highest root length (2.86 cm) were achieved on half MS medium fortified with 0.5 mg/l NAA + 1.0 mg/l IBA + 1 g/l AC. Maximum survival percentage was recorded in the hardening media which contains sand, soil and FYM in the ratio of 1 : 2 : 1. This protocol may be used for large scale production of genuine and quality planting materials. Bangladesh J. Bot. 55(2): 437-440, 2026 (June)